The Effect of Think Pair Share Learning Model on Informatics Learning Outcomes of Junior High School Students - Yunita, Elisa; Nirawana, I Wayan Sugianta (Jayapangus Press, 2025)
This study was motivated by the low learning achievement of class VIII students in Informatics subjects at Junior High School 6 Samarinda. This study aimed to determine the effect of the Think Pair Share (TPS) learning model assisted by Canva media on student learning outcomes. The method used is a Quasi-Experimental design with two different groups, namely the experimental class that applies the Think Pair Share model and the control class that uses conventional methods. Data were collected through pre-test and post-test, then analyzed using normality test, homogeneity test, and hypothesis test (Independent Sample T-Test) with the SPSS Version 25 program. The results showed that the average Post-Test score of students in the experimental class reached 77.34, exceeding the Minimum Competency Criteria set. This finding shows that the application of Think Pair Share supported by Canva media significantly improves student learning outcomes compared to conventional methods. Therefore, this strategy is recommended to be applied to other subjects to improve learning effectiveness.